Reduced functional independence and multimorbidity increases the risk of severe infection among older patients with Omicron: a multicenter retrospective cohort study - Wan Yu; Runnian Huang; Shuning Sun; Li Bu; Xin Chen; Yunhua Di; Shuwu Lin; Qian Li; Yang Yang; Xingyue Ye; Wenxu Wang; Rui Ren; et al. (BMC Geriatrics)
Abstract Background Multimorbidity and physical function in older adults have been identified as associated with coronavirus disease 2019 (COVID-19) outcomes. This study aimed to investigate whether multimorbidity affects the association of impaired functional independence (FI) with critical COVID-19 among older inpatients during the peak of Omicron infection in China. Methods This is a multicentre, retrospective cohort study in northeastern China. Patients aged ≥ 60 years, who were diagnosed with COVID-19 at the time of admission or during hospitalisation. The Barthel index was used to assess FI. Patients were classified into independent, mildly dependent, moderately dependent, and severely dependent groups. Disease severity was classified as critical, severe, and non-severe and combined into severe or critical and non-severe. Binary logistic regression analysis was used to investigate any correlation between FI and disease severity. Patients were further stratified by presence or absence of multimorbidity. Findings In this study, of 1598 patients, 530 (33.17%) developed severe or critical infections during the entire hospital stay. Patients with severe dependency had 7.39 times (95% CI: [4.60, 12.15]) higher risk of serious or critical infections than those without dependency. An interaction was noted between reduced FI and multimorbidity (p for interaction < 0.001). Compared to non-multimorbid patients (OR = 3.71, 95% CI: [1.58, 9.16]), multimorbid patients (OR = 10.04, 95% CI: [5.63, 18.57]) had a more pronounced risk of severe or critical infection. Conclusions Our results provide further scientific evidence on the association between FI, multimorbidity, and disease severity in older COVID-19 patients, contributing to future health decision-making for COVID-19 and other infectious diseases.